Globalization, Economic Development, and Ecological Footprint in Tunisia: A QARDL Approach (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This study examines the asymmetric effects of globalization dimensions (economic, social, political) and foreign direct investment on Tunisia's ecological footprint from 1979 to 2021 using the Quantile Autoregressive Distributed Lag (QARDL) approach. Moving beyond conventional mean-based estimates, our results reveal heterogeneous impacts across environmental stress regimes. Economic globalization and FDI increase environmental degradation at low pressure quantiles (τ = 0.25), but this relationship reverses at high pressure levels (τ = 0.75), suggesting a conditional Environmental Kuznets Curve trajectory. The findings demonstrate that the relationship between globalization and the environment is not uniform, but rather varies substantially with ecological conditions. We advocate for tailored policy strategies, including stringent FDI regulation in polluting sectors and incentives for green technology transfer. Enhancing social and political globalization dimensions emerges as crucial for aligning economic integration with ecological sustainability.